Altered features of neurotransmitters: NPY, α-MSH, and AgRP in type 2 diabetic patients with hypertension. Issue 5 (May 2020) - Li, Baoxin; Ma, Shuang; Guo, Shuqin; Li, Na; Liu, Dandan; Wang, He; Zhai, Na; Zhang, Yunliang
Objective: To investigate the features of neuropeptide Y (NPY), α-melanocyte stimulating hormone (α-MSH), and agouti-related protein (AgRP) in type 2 diabetes mellitus (T2DM) patients with hypertension. Methods: Patients with T2DM (n = 384) and healthy volunteers (n = 80) were enrolled into this study. Serum NPY, α-MSH, and AgRP levels were detected using ELISA. Results: Significantly higher NPY and lower α-MSH and AgRP levels were observed in patients with diabetes compared with those without diabetes, and the mean NPY levels increased, while α-MSH and AgRP levels decreased, with the development of hypertension compared with diabetic patients without hypertension. α-MSH and AgRP levels decreased with an increase in blood pressure in hypertension compared with the non-hypertension patients. Multiple stepwise linear regression analysis showed that NPY, α-MSH, and AgRP levels were closely associated with blood pressure and glucose control. Receiver operating characteristic (ROC) curve analyses indicated that α-MSH may be a better marker compared with NPY and AgRP for regulating glucose and blood pressure and to distinguish between T2DM patients with and without hypertension. Conclusion: NPY, α-MSH, and AgRP might play different roles and be closely related to the occurrence and development of diabetes and hypertension.